Every reader his book – every book its reader? Notions on readers' advisory and audience development in Danish public libraries. (September 2015) - Kann-Rasmussen, Nanna; Balling, Gitte
Collections are no longer the main attraction in libraries, and libraries are working to find new paths to tread. One strategy is to focus on reading and literature in new and surprising ways. The aim of this article is to enrich an understanding of activities situated in the span between readers' advisory and audience development. This is achieved through an analysis of opinions and reflections expressed by 13 managers and librarians in all six county libraries in Denmark. The interviews are analysed through the model which merges three concepts: cultural policy, new public management and professional logics. Our findings show that Danish librarians' views on readers' advisory and audience development strike a balance between the experience and empowerment rationales with a prevailing focus on users. A user orientation and focus on user experiences have created a situation wherein the notions of passion, commitment, enthusiasm become central to the work of librarians who champion and manage these activities. However, this strategy has limitations related to the choice of content and intended user groups. Audience development, founded on dedication and experience, tends to cater for users who look and think like librarians.